Effectiveness of the application of biostimulants in snap bean under water stress - Hernández-Figueroa, Karla Ivonne; Sánchez-Chávez, Esteban; Ojeda-Barrios, Damaris Leopoldina; Chávez-Mendoza, Celia; Muñoz-Márquez, Ezequiel (Revista Mexicana de Ciencias Agrícolas, 2022)
Water stress is one of the main factors that affect both the growth and productivity of agricultural crops. An innovative alternative to improve resistance to this water stress is the application of biostimulants. The objective of this work was to evaluate the effectiveness of biostimulants on the growth, yield, content, and water use efficiency (WUE) at different levels of water stress in the ‘Strike’ snap bean plant. The experiment was carried out under greenhouse conditions in Delicias, Chihuahua during the August-September period of 2021. A completely randomized experimental design was used and the treatments consisted of three types of irrigation: at 100% of field capacity (CC, for capacidad de campo), without water stress and at 75 and 50% of CC, in these treatments with water deficit, the biostimulants: nanoparticles of zinc oxide plus chitosan, Codasil®, Osmoplant®, Stimplex® and salicylic acid, were applied foliarly. The results obtained indicate that the best treatment applied was CC75 + nano Zn + chitosan since it favored the greater accumulation of biomass, fruit production, water content and the efficiency of water use in snap bean plants cv. Strike, which allowed it a better adaptation and tolerance to water stress compared to the treatments CC50 + Stimplex® and CC75 + Stimplex®, that probably the negative effects of water stress were greater than the benefits of the Stimplex® biostimulant applied. Finally, it is concluded that the nanoparticles of zinc oxide plus chitosan was the most efficient biostimulant to relieve and tolerate the effects of water stress, so it is considered an innovative alternative to maintain and improve the growth and production of the crop against water stress problems.